Prognostic impact of miR-17-5p and miR-20a-5p in NSCLC diverge in subgroups according to lymph node status - Førde, Dagny; Kilvær, Thomas; Pedersen, Mona Irene; Lombardi, Ana Paola; D’arsiè, Irene; Paulsen, Erna-Elise; Busund, Lill-Tove Rasmussen; Rakaee, Mehrdad; Dønnem, Tom; Andersen, Sigve (Frontiers in Oncology, 2025)
IntroductionMicroRNAs (miRs) are short non-coding, functional RNA molecules that regulate gene expression. Different miRs are frequently dysregulated and implicated in the development and outcome of non-small cell lung cancer (NSCLC). We investigated the prognostic and functional aspects of miR-17-5p and miR-20a-5p by.Methodsin situ hybridization in a large, well-characterized cohort of resected NSCLC patients and through overexpression in two NSCLC cell lines.ResultsIn the overall cohort, we observed no prognostic impact of miR-17-5p and miR-20a-5p in univariate analyses, while high expression of miR-20a-5p was associated with a positive outcome in multivariate analyses (HR 0.732, 95% CI 0.544–0.986, p = 0.040). In subgroup analyses, high expression of miR-20a-5p was associated with a positive prognosis in patients with lung squamous cell carcinoma and lymph node metastases (N+). Interestingly, miR-17-5p was associated with a poor prognosis in patients without lymph node metastases (N0), while no prognostic impact was observed in N+ patients. In cell line studies, overexpression of miR-17-5p did not influence proliferation but led to increased invasion in both investigated cell lines. Overexpression of miR-20a-5p led to decreased proliferation in one of two investigated cell lines and, like miR-17-5p, increased invasion.DiscussionOverall, our results suggest that the prognostic role of miR-17-5p and miR-20a-5p in early-stage NSCLC is context-dependent. Consequently, further studies are needed to elucidate the role of these miRs during NSCLC carcinogenesis. Clinical implementation should not be initiated until their role in different disease settings is sufficiently understood.